Investigation of environmental disturbances and fluctuations in coastal environments - Maria Sierks; Papa Oumar Djibril Diallo; Polette Aguilar Muñoz; Camila Aravena; Christian Burmeister; Olivier Crispi; Camila Fernández; Maëlann Gouriou; Christiane Hassenrück; Alizée Jamont; Emile Laymand; Mara D Maeke; et al. (PANGAEA, 2025)
Coastal marine environments — including lagoons, fjords, and estuaries — are characterized by pronounced environmental variability, with fluctuations in salinity, temperature, and nutrient levels shaping microbial community structure and function. To explore these dynamic systems, we sampled 26 sites between December 2021 and January 2023 along the coasts of France and Chile, spanning lagoons, estuaries, fjords, harbours, and both coastal and offshore marine environments. Surface waters were collected using either Niskin bottles or polycarbonate carboys, with additional deeper layers obtained at three sites. Monthly sampling at six French sites enables the assessment of seasonal dynamics. The presented dataset captures multiple environmental gradients, ranging from terrestrial–marine transitions and salinity fluctuations to eutrophication level, seasonal, geographic and disturbance-related variation. A total of 116 samples were analysed for 13 environmental parameters alongside metabarcoding and metagenomic sequencing. Temperature and salinity were recorded in the field immediately after sampling. Chlorophyll a was quantified fluorometrically following acetone extraction (Holm-Hansen et al. 1965; Lorenzen 1967). Dissolved organic carbon (DOC) was measured using high-temperature catalytic oxidation (Benner and Strom 1993) with a TOC analyser. Fluorescent dissolved organic matter (fDOM) peaks T and C (as proxy for protein like and humic like DOM, respectively) were quantified with a Jasco FP-8500 spectrofluorometer (Coble 1996). Leucine incorporation rates were determined via the centrifugation method (Smith and Azam 1992), and respiration rates were estimated via oxygen consumption in 5 ml glass vials using PreSens OxoDishes and a SensorDish® Reader. Inorganic nutrients were analyzed using a QuAAtro39 or AA3HR autoanalyzer (Grasshoff et al. 2009; Aminot and Kérouel 2007).